2018
DOI: 10.1371/journal.pone.0194698
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping for eyespot disease in US Pacific Northwest winter wheat

Abstract: Eyespot, caused by the soil-borne necrotrophic fungi Oculimacula yallundae and O. acuformis, is a disease of major economic significance for wheat, barley and rye. Pacific Northwest (PNW) winter wheat (Triticum aestivum L.) grown in areas of high rainfall and moderate winters is most vulnerable to infection. The objective of this research was to identify novel genomic regions associated with eyespot resistance in winter wheat adapted to the PNW. Two winter wheat panels of 469 and 399 lines were compiled for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Regression analyses showed the direct relationship between increasing number of favorable alleles and increased snow mold tolerance demonstrating an additive response. Previously, pyramiding favorable alleles was observed to increase resistance for stripe rust (Naruoka et al, 2015) and eyespot disease (Lewien et al, 2018) for the same population of US PNW winter wheat lines. Lines differing at a single locus (e.g., lines with eight favorable alleles vs. lines having nine) had similar levels of tolerance, suggesting that additive effects for these alleles might not be enough for significant differences to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regression analyses showed the direct relationship between increasing number of favorable alleles and increased snow mold tolerance demonstrating an additive response. Previously, pyramiding favorable alleles was observed to increase resistance for stripe rust (Naruoka et al, 2015) and eyespot disease (Lewien et al, 2018) for the same population of US PNW winter wheat lines. Lines differing at a single locus (e.g., lines with eight favorable alleles vs. lines having nine) had similar levels of tolerance, suggesting that additive effects for these alleles might not be enough for significant differences to occur.…”
Section: Discussionmentioning
confidence: 99%
“…This population consisted of club (172 lines; 37.6%) and common (286; 62.4%) wheat. The AMP was previously characterized for different traits including stripe rust resistance (Naruoka et al, 2015; Liu et al, 2018), eyespot resistance (Lewien et al, 2018), end-use quality traits (Jernigan et al, 2018), preharvest sprouting tolerance, and low falling number (Martinez et al, 2018). Additionally, 295 winter wheat breeding lines from the Washington State University (WSU) Winter Wheat Breeding and Genetics Program evaluated for snow mold tolerance between 2015 and 2018 were used as selection candidates (TST lines) for independent validations.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of these lines were common wheat (284; 62%), whereas the remaining lines were club wheat (172; 38%). This population has been characterized previously for different traits such as grain yield [35], snow mold tolerance [11], eyespot resistance [36], and end-use quality traits [37].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Interaction of QTL for P. capsici resistance have been well established in previous studies in chile pepper [ 45 , 51 – 53 ], and indicates the potential of combining favorable alleles to improve disease resistance. In other crops such as winter wheat ( Triticum aestivum L.), pyramiding resistant alleles has been demonstrated to increase resistance or tolerance to various diseases such as stripe rust (causative agent: Puccinia striiformis [ 54 ], eyespot disease ( Oculimacula yallundae and Oculicmacula acuformisi ) [ 55 ]; and snow mold ( Microdochium [ Fusarium ] nivale ) [ 56 ]. The QTL interactions identified in the current study have not been reported elsewhere, and hence could represent novel genomic regions showing additive effects that could be targeted for future breeding and selection for improved P. capsici resistance.…”
Section: Discussionmentioning
confidence: 99%